Ruderal Resilience: Applying a Ruderal Lens to Advance Multispecies Urbanism and Social-Ecological Systems Theory - Kennedy, Christopher (Frontiers in Built Environment, 2022)
As global urbanization accelerates, cities have become increasingly complex and hybridized, and host to novel urban landscape forms such as informal greenspaces or novel ecosystems that support ruderal and spontaneous vegetation. Researchers have documented the ecosystem services or benefits these systems provide, as well as the tradeoffs or disservices associated with biotic globalization. Despite evidence of their co-benefits, fragmented knowledge and biased views of these novel ecological forms contributes to an underestimation of their social-ecological role and potential for serving as a model for resilient and nature-based urban design and planning. The social-ecological systems discourse has improved understanding of these emerging conditions, yet may benefit from an attunement to a multispecies perspective, an ecosystem-based approach to urban planning and governance that recognizes the interdependencies of humans and other organisms. This article explores the potential social-ecological role of ruderal landscapes in facilitating this transition, referred to as ruderal resilience, as well as recent research in SES and resilience theory that may help advance concepts such as multispecies urbanism and planning. The aim is to consider the potential for spontaneous ecological self-organization to serve as a device for reinvigorating relationships with urban ecological commons and advancing social-ecological systems theory.